Seroprevalence of antibodies against SARS-CoV-2 in the Valencian Community (Spain) as of October 2022 - Aníbal García-Sempere; Estela Giménez; Hermelinda Vanaclocha; Ramón Limón; Salvador Peiró; David Navarro (Elsevier, 2023)
Objective: To estimate the seroprevalence of SARS-CoV-2 antibodies in the Valencian Community (Spain) in October 2022, when BA.5 was the predominant variant. Method: Cross-sectional, region-wide, population-based serosurvey study in 88 randomly selected primary care centers of the Valencian Community. Results: Seroprevalence of anti-nucleocapsid (indicative of past infection) and total receptor binding domain (indicative of past infection or vaccination) antibodies was 71.0% (confidence interval [CI]: 67.8-74.2) and 98.4% (CI: 97.5-99.3), respectively. 66.7% (CI: 63.4-70.0) of the population shows hybrid immunity, but only 43.2% in those 80 and over. Conclusions: The high proportion of hybrid immunity detected is relevant for public health strategies. A second vaccination booster was advisable in the elderly population. Resumen: Objetivo: Estimar la seroprevalencia de anticuerpos frente al SARS-CoV-2 en la Comunidad Valenciana (España) en octubre de 2022, cuando BA.5 era la variante predominante. Método: Estudio transversal de base poblacional de ámbito autonómico en 88 centros de atención primaria de la Comunidad Valenciana seleccionados aleatoriamente. Resultados: La seroprevalencia de anticuerpos antinucleocápside (indicativos de infección previa) y frente al dominio de la unión al receptor (indicativos de infección o vacunación) fue del 71,0% (intervalo de confianza [IC]: 67,8-74,2) y del 98,4% (IC: 97,5-99,3), respectivamente. El 66,7% (IC: 63,4-70,0) de la población mostraba inmunidad híbrida, pero solo el 43,2% de los mayores de 80 años. Conclusiones: La alta proporción de inmunidad híbrida detectada era relevante para las estrategias de salud pública, pero era aconsejable un segundo refuerzo de vacunación en la población anciana.